(untitled) (ASEAN Engineering Journal, 2014)
This paper introduces a nonlinear adaptive controller for tracking the welding path of a twowheeled Welding Mobile Robot (WMR) with unknown system parameters. A touch sensor that measures the errors between the WMR and the welding path is introduced. The controller is designed to drive the tracking errors to zero as fast as desired. The WMR can track any smooth curved welding path at a constant welding velocity. The effectiveness of the proposed controller is proved through simulation and experimental results.